Regulation of Sodium and Potassium Transport in Phytohemagglutinin-Stimulated Human Blood Lymphocytes - Segel, George B. (1979)
Phytohemagglutinin (PHA) or concanavalin A treatment of lymphocytes causes an increase in membrane permeability so that the leak rates of Na and K increase 1.5- to 2-fold. Active Na and K transport increase proportionately in response to the increased membrane permeability. We have examined the role of lymphocyte Na concentration in sustaining the increased Na and K transport observed after PHA treatment. Cell Na concentration increases from 14.8 to 20.5 mmol/liter cell water in PHA-treated lymphocytes (P < 0.001). Four lines of evidence suggest that the 5-6 mmol/liter cell water increase in lymphocyte Na accounts for the increase in active Na and K transport in mitogen-treated lymphocytes. First, PHA does not increase directly the maximal Na, K-ATPase activity of isolated lymphocyte membrane vesicles. Second, when the Na concentration is increased by 6 mmol/liter cell water in unstimulated lymphocytes, Na and K transport increase nearly twofold. Third, the cell Na concentration (15 mmol/liter cell water) is near the K(m) for Na activation of the Na, K-ATPase in lymphocyte membranes. The ATPase activity thus, is capable of increasing as the cell Na rises above normal. Fourth, if lymphocytes are incubated in a medium containing a low Na concentration, K transport does not maintain the internal K concentration and the fall in cell K is accentuated in PHA-treated lymphocytes. These studies indicate that the adaptive acceleration of Na and K transport in mitogen-treated lymphocytes is mediated by a small increase in cell Na.